The Analysis Study of Risk Factor, Management and Outcome of Obesity in Children: A Comprehensive Systematic Review - Saleh, Hendra; Pasambo, Trisnawanta Asih; Leo, Henry (International Medical Journal Corp. Ltd, 2024)
Background: Overweight and obesity under 18 years of age has been linked to an increased risk of premature mortality from middle adulthood onward. The aim: The aim of this study to show about risk factor, management and outcome of obesity in children. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: the broad principle of treatment is to adjust the chronically positive energy balance. While lifestyle and behavior modifications with dietary changes and increased physical activity are the integral part of obesity management, the efficacy and sustainability are limited, especially for those with severe obesity. With emerging evidence on new pharmacological agents, it is hoped that obesity management in children could be improved in the future.